Design of multiphase interleaved DC-DC converter - Tang, Tobias Bo Yao (2018)
The power requirements for different pieces of technology that is used every day is different, with different components within devices operating at different power ratings. However, there is usually one battery pack or power supply supplying power to devices with different requirements. As a result, converters that are able to provide a regulated supply are required to be used in these scenarios. Additionally, since the supply voltage of battery commonly used in mobile devices reduces as power is being consumed, the step-up or step-down converter that is being used should be able to work within a range of input voltages. DC-DC converters provide an opportunity to do this. There exists a wide variety of DC-DC converters that can regulate specific voltages from a small range of input voltage, either stepping up (boost) or stepping down (buck) the input voltage. On top of that, the efficiency that switched mode converters can provide is high, in the range of 85% and above. High efficiency, coupled with the ability to integrate most of the circuit, makes DC-DC converters a suitable choice for a wide variety of applications. For this project, a multiphase interleaved buck DC-DC converter will be constructed using 0.18um CMOS technology. Interleaving buck DC-DC converters addresses the issue of high loads when using a single buck converter by distributing it over multiple phases. Lower current load per phase would also result in better heat dissipation, eliminating the need for heat dissipation methods. Additionally, phase interleaving would reduce the output ripple commonly observed in DC-DC converter outputs. This report documents the design process when creating a multiphase interleaving buck converter. The report would first cover the different components that makes up the multiphase converter. After which the design of each component would be looked at and the single-phase converter would be simulated in order to observe the improvements in performance with the multiphase converter.